DAKWAH AND LAyANAN MASyARAKAT: OutcOme SkillS SARjANA DAKWAH - Muchammadun Muchammadun (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2017)
The distinctive knowledge, skills, and ethics of departments in Fakultas Ilmu Dakwah is an important factor to sustain a professional education. One of the professional activities is Higher Education services, of which their built environment of teaching and learning process will largely affect their outcomes.In line with the transformation of IAINs to fully-fledged universities, the quality of Wissenschaft is partly be defined from what outcome skills are set up. This is particularly important for departments of faculties where people have already labeled them as sole religious studies such as Fakultas Ilmu Dakwah. This paper argues that thedistinctive epistemology of religion and science bears a consequence of outcome skills of critical thinking and facilitation.